Collectifs logistiques et territoires dans les circuits courts alimentaires de proximité : la robustesse de la coopération analysée au prisme des communs - Céline Raimbert; Gwenaëlle Raton (Développement Durable et Territoires)
New collectives are identified in the short food supply chains. Their goal is to organize local products supply at a territorial scale. We consider them new because they do not lie on previous social capital and they imply new actors to collaborate with. The logistical function is also more central. This ambitious challenge addresses a cooperation problem and demands new governance systems. Considering such challenges, this paper aims at questioning the robustness of the cooperation mechanisms of these new collectives. We consider then that the cooperation robustness insures the sustainability of the collective actions such as its territorial stake. Our approach involves studying three logistical collectives from a Commons perspective and using two analysis frameworks. The first one evaluates their cooperation level, the second one identifies institutional variables of the cooperation. Finally, we discuss territorial actors’ contribution to the production of collective action and their eventual drivers.